Analisis Kesalahan Konseptual Dan Prosedural Dalam Eksperimen Berbasis Laboratorium Virtual Fisika: Sebuah Kajian Literatur - Heni Yulianti; Handini Handini; Alpina Pebrianti; Gunawan Gunawan; Nina Nisrina (Indonesian Publication Center, 2023)
Physics learning requires both conceptual understanding and procedural skills in conducting experiments. However, limited laboratory facilities often become an obstacle in implementing practicum activities, so virtual laboratories are used as an alternative to support experimental learning. This study aims to analyze students’ conceptual and procedural errors in conducting virtual laboratory–based experiments in physics learning through a literature review. The method employed is a literature study by examining 15 relevant scientific journal articles. The results show that conceptual errors include misconceptions of physics concepts, difficulties in relating simulations to theory, and errors in interpreting experimental results. Meanwhile, procedural errors include inaccuracies in following experimental steps, mistakes in setting variables, and difficulties in analyzing data. Therefore, appropriate instructional strategies are needed, such as structured scaffolding, clear experimental guidelines, conceptual discussions before and after practicum, and teacher guidance during the use of virtual laboratories. Thus, the proper use of virtual laboratories can enhance students’ conceptual understanding and experimental skills.